CURRENT ISSUES OF TEACHING FOREIGN LANGUAGES AND INNOVATIVE TECHNOLOGIES IN EDUCATION - Niyazova Minara Bakhramovna (Bright Mind Publishing, 2025)
Teaching foreign languages is a complex and multifaceted process that requires special attention and approach from both the teacher and the student. However, despite all efforts, it has recently become clear that traditional teaching methods are ineffective and do not always achieve the desired results. Foreign languages are one of the key competencies in today’s globalizing world and play a leading role. This article examines the current issues related to teaching foreign languages, such as the inefficiency of traditional teaching methods, lack of student motivation, assessment problems, and others. However, there are many methods and approaches that can help teachers overcome these issues and make the learning process more effective and engaging for students.
Keywords: Foreign languages, communicative competence, teaching, assessment problems, approach.